2020
DOI: 10.1186/s13643-020-1286-z
|View full text |Cite
|
Sign up to set email alerts
|

From the sticky floor to the glass ceiling and everything in between: protocol for a systematic review of barriers and facilitators to clinical academic careers and interventions to address these, with a focus on gender inequality

Abstract: on behalf of the project teamAbstract Background: Gender inequality within academic medicine and dentistry is a well-recognised issue, but one which is not completely understood in terms of its causes, or interventions to facilitate equality. This systematic review aims to identify, critically appraise, and synthesise the literature on facilitators and barriers to progression through a clinical academic career across medicine and dentistry. It will also explore interventions developed to increase recruitment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 18 publications
0
48
0
Order By: Relevance
“…17 The study adheres to social constructionist or JAMA Network Open | Diversity, Equity, and Inclusion constructivist approaches, which emphasize the importance of examining participants' understandings of their own experiences when studying any social phenomena. 18,19 We use a social constructionist conceptualization of gender, which considers the differences between women and men a product of social interactions and negotiations, rather than innate, biological differences. 20,21 The senior author conducted in-depth, semistructured interviews with 52 women academic medicine faculty members at 16 institutions across the US.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…17 The study adheres to social constructionist or JAMA Network Open | Diversity, Equity, and Inclusion constructivist approaches, which emphasize the importance of examining participants' understandings of their own experiences when studying any social phenomena. 18,19 We use a social constructionist conceptualization of gender, which considers the differences between women and men a product of social interactions and negotiations, rather than innate, biological differences. 20,21 The senior author conducted in-depth, semistructured interviews with 52 women academic medicine faculty members at 16 institutions across the US.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…[11][12][13] There is a substantial amount of literature to support that women are underrepresented in leadership positions in academia. 5,6,8,[19][20][21][22][23][24] This is independent of eld and has been documented even in elds which are predominantly comprised of women, such as pediatrics. 7 With regard to ophthalmology speci cally, our ndings are very similar to a recent study of multiple medical elds which found 36% of rst author (compared with our 37% of all, Cochrane and non-Cochrane, rst authors), and 24% of last author positions (compared with our 25% of all corresponding author positions which were most often last authors) to be held by women.…”
Section: Discussionmentioning
confidence: 97%
“…There is a substantial amount of literature to support that women are underrepresented in leadership positions in academia [5,6,8,[19][20][21][22][23][24]. This is independent of field and has been documented even in fields which are predominantly comprised of women, such as pediatrics [7].…”
Section: Discussionmentioning
confidence: 99%